Correction: Al-Lahham et al. Reference Interval for Glycated Albumin, 1,5-AG/GA, and GA/HbA1c Ratios and Cut-Off Values for Type 1, Type 2, and Gestational Diabetes: A Cross-Sectional Study. Biomedicines 2024, 12, 2651 - Yusra Al-Lahham; Waldemar Volanski; Liana Signorini; Ademir Luiz do Prado; Glaucio Valdameri; Vivian Rotuno Moure; Marciane Welter; Alexessander C. Alves; Marcel Henrique Marcondes Sari; Fabiane Gomes de Moraes Rego; Geraldo Picheth (Biomedicines)
In the original publication [...]